Studies in Legal Hadith - Yanagihashi, Hiroyuki, (Studies in Islamic Law and Society, 2019)
This book is dedicated to an analysis of seven groups of hadiths related to matters ranging from the rules concerning water used for ablution to those concerning the proof of facts in a qadi court. It has three main purposes. The first is to clarify the processes by which hadiths on a given topic were formed and developed by analyzing their isnāds and matns and by comparing them with expositions of positive law in legal manuals. Second, it seeks to explain why many hadiths exist in multiple variants and to detect the perception of traditionists about the revision of hadiths. The third purpose is to propose a methodology to estimate the extent to which traditionists accepted hadiths on a particular topic.